Simulating Surface Runoff Volume in Southern Louisiana with DRAINMOD1 - Saleh, Abdul Razak (Universiti Putra Malaysia Press, 1994)
The water management simulation model, DRAINMOD, was used to simulate surface runoff volume from a subsurface-drained plot and a non-subsurface drained plot in southern Louisiana. Seven years (1981-87) of recorded data were used in this study. The model overestimated the total surface run off volume by 7.7% and 25.1% from the subsurface-drained plot and the non-subsurface drained plot, respectively. In general, the performance of the model in simulating surface runoff volume in southern Louisiana is satisfactory.